Electronically excited states of PANH anions. Issue 22 (14th June 2015) - Theis, Mallory L.; Candian, Alessandra; Tielens, Alexander G. G. M.; Lee, Timothy J.; Fortenberry, Ryan C.
<x xml:space="preserve">Abstract</x> The singly deprotonated anion derivatives of nitrogenated polycyclic aromatic hydrocarbons are shown likely to possess dipole-bound and even valence excited states for the larger systems.